The third ventricle of the human fetal brain: Normative data and pathologic correlation. A 3D transvaginal neurosonography study. (21st June 2018) - Birnbaum, Roee; Parodi, Stefano; Donarini, Gloria; Meccariello, Gabriella; Fulcheri, Ezio; Paladini, Dario
Abstract: Objective: The objective of the study are to describe (a) the technical aspects and (b) the anatomical boundaries of the fetal third ventricle (3V) on the midsagittal sonographic view and to assess (c) different biometric parameters in normal and abnormal fetuses and (d) and their reproducibility. Methods: This study included 67 normal and 50 CNS anomalies fetuses which include (1) obstructive severe ventriculomegaly (SVM; atrial width ≥ 15 mm), (2) moderate ventriculomegaly (10‐14.9 mm), and (3) corpus callosum agenesis (ACC). All underwent transvaginal 3D neurosonography of the midsagittal view of the 3V. The following parameters were measured: area, perimeter, craniocaudal and anteroposterior (AP) diameters, interthalamic adhesion diameter (ITAD), wedge angle, and the ratio between the last 2 variables (ITAD/WA). Repeatability was also assessed. Results: The ITAD and the ITAD/WA are significantly different between normal fetuses and the SVM ( P  ≤ .001). Interthalamic adhesion diameter of ≤7.1 mm is able to identify SVM with 98.6% accuracy (CI: 0.92‐0.99). In ACC cases, the AP diameter is significantly shorter than both normal fetuses and ventriculomegaly. Intraobserver/interobserver reliability was good for most variables. Conclusions: Transvaginal neurosonography enables visualization of the normal and abnormal fetal third ventricle. An ITAD <7.1 identifies aqueductal stenosis as the likely etiology of severe ventriculomegaly with an accuracy of 98.6%. Abstract : What's already known about this topic? The third ventricle of the fetal brain is a complex‐shaped lumen, connecting the lateral and fourth ventricles. Brain malformations may change its geometry in various aspects, but these aspects do not show up on the axial view. Normative data in the fetus are scarce and include only the axial plan view. What does this study add? We describe the midsagittal view of the third ventricle and its normal anatomic surroundings, by high‐resolution transvaginal neurosonography. We assess its biometry and aspect in normal fetuses and fetuses with ventriculomegaly from different etiologies.